2011
DOI: 10.1592/phco.31.11.1045
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin for the Treatment of Plaque‐Type Psoriasis

Abstract: Oral atorvastatin 40 mg/day was not associated with therapeutic benefit when given to patients with baseline PASI scores less than 12 who were also treated with standard topical therapies. Additional trials are needed to elucidate the place of statins for the treatment of psoriasis. A larger follow-up study, as well as testing atorvastatin in patients with more intensive disease characterized by high PASI scores, is needed. Studies using higher atorvastatin doses or dose-ranging studies should also be performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Troglitazone normalized histological features in psoriasis models and the lesional phenotype in a small clinical trial [48]. The “HMG CoA reductase inhibitor” drug simvastatin was effective in a pilot study, although atorvastatin in the same class showed only a non-significant improvement in a different study [49], [50]. Salicylic acid has antifungal effects and it's used as adjuvant because of its keratolytic effect in the treatment of psoriasis [51].…”
Section: Resultsmentioning
confidence: 99%
“…Troglitazone normalized histological features in psoriasis models and the lesional phenotype in a small clinical trial [48]. The “HMG CoA reductase inhibitor” drug simvastatin was effective in a pilot study, although atorvastatin in the same class showed only a non-significant improvement in a different study [49], [50]. Salicylic acid has antifungal effects and it's used as adjuvant because of its keratolytic effect in the treatment of psoriasis [51].…”
Section: Resultsmentioning
confidence: 99%
“…Such actions of statins include inhibiting the release of inflammatory cytokines such as TNF‐α, IL‐1 and IL‐6, which are implicated in psoriasis 48 . However, clinical evidence for the effectiveness of statins on psoriasis is inconclusive 49–53 . Of note, multiple studies have also found that treatment with TNF inhibitors has no effect on patients’ lipid profiles, with additional studies reporting small increases in plasma lipid levels from TNF inhibitors 54–58 …”
Section: Discussionmentioning
confidence: 99%
“…48 However, clinical evidence for the effectiveness of statins on psoriasis is inconclusive. [49][50][51][52][53] Of note, multiple studies have also found that treatment with TNF inhibitors has no effect on patients' lipid profiles, with additional studies reporting small increases in plasma lipid levels from TNF inhibitors. [54][55][56][57][58] Medications may modulate the relationship between psoriasis and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Researchers have also investigated the possibility of using statins in inflammatory conditions as diverse as psoriasis 3 and multiple sclerosis, 4 although the evidence remains limited. Hypotheses about the mechanisms of these anti-inflammatory effects include the inhibition of proinflammatory cytokines and reduced T cell activation.…”
mentioning
confidence: 99%